THE INFLUENCE OF ENGLISH FINE CERAMICS OF THE XVIII CENTURY ON THE FORMATION OF PRODUCTS OF ZHOVKVA AND GLINSK - Rudenchenko, Alla; Prokhorova, Nataliia (Theory and practice of design, 2023)
Purpose. The purpose of the article is to highlight the enrichment of shaping and decoration of the porcelain-faience products of Glynsko and Zhovkva in terms of the influence on them of examples of fine ceramic works of Great Britain of the 18th century. Methodology. The research methodology is based on art history methods and approaches that make it possible to fully analyze and reveal the specifics of shaping and decorating fine ceramics of England and Ukraine. Instead, axiological, historical-chronological, historical-comparative and historical-cultural methods were used to deepen the process of transformation of local vessels and reveal the result. A cross-cultural analysis was used to compare the range of fine ceramics of leading UK manufactories, including Rill’s Semi China, Spode, Staffordshire and the works of Glsnsk and Zhovkva of the 18th–19th centuries Results. It was established that the production of ceramics produced in Glynsk was divided into the following three periods: 1) production of simple pottery ceramics, early variations of earthenware and soft porcelain; 2) mechanization of the enterprise according to new technological trends, expansion of the range of products; 3) after a long pause, the beginning of an active phase of manufacturing thin ceramic objects, the source of inspiration of which was English porcelain-faience. It was found that the last period was significant for the contribution to the general development of fine ceramics of Ukraine and bringing it to the world level. Scientific novelty. The scientific novelty of the article is related to the establishment of the uniqueness of the formation and decoration of thin-walled products of Glynsk against the background of the works of European artistic and industrial centers of the 18th–19th centuries. Practical relevance. The obtained results of the research can deepen modern intelligence on the peculiarities of the development and activity of Ukrainian porcelain- faience enterprises. Determining the design of local fine ceramics, which combined the distinctive features of folk decorative and applied art and the exploitability of prominent sites in England, which makes it possible to highlight the value of the products of Glynsk in the 19th century.